PENGARUH KONSENTRASI ZPT ALAMI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA HIJAU (Lactuca sativa L.) PADA SISTEM HIDROPONIK - Tri Wulandari; Fiana Podesta; Dwi Fitriani; Ririn Harini (BUANA SAINS, 2025)
The use of natural growth regulators offers a sustainable alternative to synthetic compounds in hydroponic systems. This study evaluates the effect of natural plant growth regulators (PGRs) from coconut water and bamboo shoot extract on the growth of green lettuce (Lactuca sativa L.) in a Deep Flow Technique (DFT) hydroponic system and determines the optimal concentration. The experiment, conducted at BPSIP from October to November 2024, used a Completely Randomized Design (CRD) with nine treatments: a control, coconut water, and bamboo shoot extracts at concentrations of 10, 20, 30, and 40 ml L?¹, with three replications. The results showed that PGR applications did not significantly affect most parameters, including plant height at 21 and 35 days after transplanting (DAT), leaf dimensions, fresh shoot weight, and root weight. However, significant effects were observed on plant height at 28 DAT and leaf number at 28 and 35 DAT. Coconut water at 10 ml L?¹ produced the best response for these parameters. These findings confirm that the effectiveness of natural PGRs in DFT hydroponics is concentration-dependent and that under optimal nutrient conditions, their addition does not consistently enhance lettuce growth.